Association between knee- and hip-extensor strength and running-related injury biomechanics in collegiate distance runners - Moffit, T. J.; Montgomery, M. M.; Lockie, R. G.; Pamukoff, D. N. (Journal of Athletic Training, 2020)
Context: Running-related injuries are common in distance runners. Strength training is used for performance enhancement and injury prevention. However, the association between maximal strength and distance-running biomechanics is unclear. Objective: To determine the relationship between maximal knee- and hip-extensor strength and running biomechanics previously associated with injury risk. Design: Cross-sectional study. Setting: Research laboratory. Patients or Other Participants: A total of 36 collegiate distance runners (26 men, 10 women; age = 20.0 ± 1.5 years, height = 1.74 ± 0.09 m, mass = 61.97 ± 8.26 kg). Main Outcome Measure(s): Strength was assessed using the 1-repetition maximum (1RM) back squat and maximal voluntary isometric contractions of the knee extensors and hip extensors. Three-dimensional running biomechanics were assessed overground at a self-selected speed. Running variables were the peak instantaneous vertical loading rate; peak forward trunk-lean angle; knee-flexion, internal-rotation, and -abduction angles and internal moments; and hip-extension, internal-rotation, and -adduction angles and internal moments. Separate stepwise linear regression models were used to examine the associations between strength and biomechanical outcomes (?R2) after accounting for sex, running speed, and foot-strike index. Results: Greater 1RM back-squat strength was associated with a larger peak knee-flexion angle (?R2 = 0.110, ?P = .045) and smaller peak knee internal-rotation angle (?R2 = 0.127, ?P = .03) and internal-rotation moment (?R2 = 0.129, ?P = .03) after accounting for sex, speed, and foot-strike index. No associations were found between 1RM back-squat strength and vertical loading rate, trunk lean, or hip kinematics and kinetics. Hip- and knee-extensor maximal voluntary isometric contractions were also not associated with any biomechanical variables. Conclusions: Greater 1RM back-squat strength was weakly associated with a larger peak knee-flexion angle and smaller knee internal-rotation angle and moment in collegiate distance runners. Runners who are weaker in the back-squat exercise may exhibit running biomechanics associated with the development of knee-related injuries.